2004
DOI: 10.4049/jimmunol.173.5.3467
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Is a Key Transcription Factor That Regulates Antioxidant Defense in Macrophages and Epithelial Cells: Protecting against the Proinflammatory and Oxidizing Effects of Diesel Exhaust Chemicals

Abstract: The proinflammatory effects of particulate pollutants, including diesel exhaust particles (DEP), are related to their content of redox cycling chemicals and their ability to generate oxidative stress in the respiratory tract. An antioxidant defense pathway, which involves phase II enzyme expression, protects against the pro-oxidative and proinflammatory effects of DEP. The expression of enzymes, including heme oxygenase-1 (HO-1) and GST, is dependent on the activity of a genetic antioxidant response element in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
343
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 416 publications
(361 citation statements)
references
References 67 publications
15
343
1
2
Order By: Relevance
“…Further, as performance validation of the mVACES is the principal focus of this work, discussion of the physical and chemical characteristics of the observed aerosol is subsequently limited. Our observations, however, are consistent with extensive measurements previously reported at the same site (Sardar et al 2005;Miguel et al 2004). …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Further, as performance validation of the mVACES is the principal focus of this work, discussion of the physical and chemical characteristics of the observed aerosol is subsequently limited. Our observations, however, are consistent with extensive measurements previously reported at the same site (Sardar et al 2005;Miguel et al 2004). …”
Section: Resultssupporting
confidence: 81%
“…Given the complexity of the urban aerosol, achieving consistent concentration enrichment factors and performance by the mVACES provides a more comprehensive validation than can be achieved in the laboratory. Of particular interest in the present study was the ability of the mVACES to concentrate effectively species such as trace elements and metals as well as organic compounds, such as organic carbon (OC) and polycyclic aromatic hydrocarbons (PAH), all of which are associated with health effects attributable to PM (Pope et al 2002;Li et al 2003Li et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…HMGB1, a well-characterized cytokine with pleiotropic function, is a crucial late mediator of mortality in sepsis (32). Secretory HMGB1 augments proinflammatory response and promotes inflammation and tissue injury (33).The level of HMGB-1, was also significantly higher in LysMNrf2 2/2 compared with LysM-Keap1 2/2 . Both mice and clinical studies have documented that the balance of proinflammatory and antiinflammatory cytokines is a better predictive marker of severity and mortality in sepsis rather than a single mediator (23,34).…”
Section: Discussionmentioning
confidence: 78%
“…To this date, however, there appears to be heterogeneity in particulate matter (PM) concentrations and PMassociated health effects between locations within an urban setting, which raises considerable uncertainties as to whether PM mass, number, size, bulk or surface chemistry are the appropriate metrics associated with PM toxicity. For example, recent studies have shown that atmospheric ultrafine particles (with physical diameter o100 nm) have the potential for eliciting adverse health effect (Oberdo¨rster and Utell, 2002;Li et al, 2003Li et al, , 2004Xia et al, 2004). Recent epidemiological studies by Peters et al (1997) have demonstrated a higher association between health effects and exposures to ultrafine particles compared to accumulation mode or coarse particles.…”
Section: Introductionmentioning
confidence: 99%